Boosting resource use efficiency, soil fertility, food security, ecosystem services, and climate resilience with legume intercropping: a review - Akchaya, K.; Parasuraman, P.; Pandian, Kannan; Vijayakumar, S.; Thirukumaran, K.; Mustaffa, Mohamed Roshan Abu Firnass; Rajpoot, Sudhir Kumar; Choudhary, Anil K. (Frontiers in Sustainable Food Systems, 2025)
Adopting sustainable agricultural practices that enhance productivity while preserving ecosystem services is essential to ensure food security for a growing global population and address environmental challenges. This review examines the impact of legume intercropping on nitrogen (N) fixation, soil physio-chemical properties, water retention, pest and disease control, and crop yield across diverse agro-climatic zones and cropping systems. The findings consistently demonstrate that integrating legumes into the cropping system improves soil health by reducing bulk density, breaking up hardpan layers, reducing erosion, increasing soil organic matter, and fixing atmospheric nitrogen ( 125 kg N/ha/season) reducing the need for inorganic N fertilizers. It boosts crop yields by 30–35% (in terms of main crop equivalent yield) and land productivity per unit area and time, mitigates total crop loss, and promotes biodiversity. It also improves water use efficiency by 20–25% and enhances nutrient use efficiency by 25–30%. Additionally, legume intercropping reduces yield losses from pests and diseases by 20–25% compared to sole cropping systems. The practice bolsters crop resilience through ecological processes like bio-littering, bio-ploughing, bio-irrigation, and bio-pumping (the “4Bs”), which are valuable for adapting to climate variability. However, research gaps remain, particularly in the optimal selection of legume species for specific regions, suitable agronomic practice for each system, and addressing socio-economic barriers to widespread adoption.